Optimalisasi Pengawasan Pengelolaan Keuangan Daerah di Kabupaten Sidoarjo - Luchman Sanjaya (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
This study aimed to determine, describe and analyze the optimization of Inspectorate function in the Sidoarjo Regency in conducting oversight of financial management as well as strategies to overcome the weaknesses of local finance control by the Inspectorate in Sidoarjo Regency. This research used descriptive research through a qualitative approach. Data collected through the literature study come from primary data and secondary data. The results showed the optimization of supervision and financial management by the Inspectorate in Sidoarjo Regency has not been run in accordance with the monitoring mechanism and the regional finance authority. Some strategies are arranged to overcome obstacles in the control and management of local finance by Inspectorate Sidoarjo regency include: using a personalized approach to the audit in carrying out checks on the local work unit (SKPD), e-audit approach, increase of the inspector/auditor of local work unit (SKPD), the budgeting process on the inspection costs more planned, as well as an understanding of the apparatus is associated with budgeting.